Answer:
![sin (-x) cos (-x) csc (-x) =cos(x)](https://tex.z-dn.net/?f=sin%20%28-x%29%20cos%20%28-x%29%20csc%20%28-x%29%20%3Dcos%28x%29)
Step-by-step explanation:
We know by definition that the cosine is an even function, therefore
![cos (-x) = cos (x)](https://tex.z-dn.net/?f=cos%20%28-x%29%20%3D%20cos%20%28x%29)
We also know that the sin is an odd function, therefore
![sin (-x) = -sin (x)](https://tex.z-dn.net/?f=sin%20%28-x%29%20%3D%20-sin%20%28x%29)
By definition:
![cscx = \frac{1}{sinx}.](https://tex.z-dn.net/?f=cscx%20%3D%20%5Cfrac%7B1%7D%7Bsinx%7D.)
Then:
![csc(-x) = \frac{1}{sin(-x)}.](https://tex.z-dn.net/?f=csc%28-x%29%20%3D%20%5Cfrac%7B1%7D%7Bsin%28-x%29%7D.)
![csc(-x) = -\frac{1}{sin(x)}.](https://tex.z-dn.net/?f=csc%28-x%29%20%3D%20-%5Cfrac%7B1%7D%7Bsin%28x%29%7D.)
Using these trigonometric properties we can simplify the expression
![sin (-x) cos (-x) csc (-x)= -sin(x)cos(x)*(-\frac{1}{sin(x)})\\\\sin (-x) cos (-x) csc (-x)=cos(x)](https://tex.z-dn.net/?f=sin%20%28-x%29%20cos%20%28-x%29%20csc%20%28-x%29%3D%20-sin%28x%29cos%28x%29%2A%28-%5Cfrac%7B1%7D%7Bsin%28x%29%7D%29%5C%5C%5C%5Csin%20%28-x%29%20cos%20%28-x%29%20csc%20%28-x%29%3Dcos%28x%29)
He needs to earn ; 77.99-20= 57.99 dollars
so in one week there are 2 weekends; so he earns 6×3×2 = 36 dollars
so no of week = 57.99÷ 36= 1.6 weeks
so weeks are in natural no thus it will take him 2 weeks !!
Treat the matrices on the right side of each equation like you would a constant.
Let 2<em>X</em> + <em>Y</em> = <em>A</em> and 3<em>X</em> - 4<em>Y</em> = <em>B</em>.
Then you can eliminate <em>Y</em> by taking the sum
4<em>A</em> + <em>B</em> = 4 (2<em>X</em> + <em>Y</em>) + (3<em>X</em> - 4<em>Y</em>) = 11<em>X</em>
==> <em>X</em> = (4<em>A</em> + <em>B</em>)/11
Similarly, you can eliminate <em>X</em> by using
-3<em>A</em> + 2<em>B</em> = -3 (2<em>X</em> + <em>Y</em>) + 2 (3<em>X</em> - 4<em>Y</em>) = -11<em>Y</em>
==> <em>Y</em> = (3<em>A</em> - 2<em>B</em>)/11
It follows that
![X=\dfrac4{11}\begin{bmatrix}12&-3\\10&22\end{bmatrix}+\dfrac1{11}\begin{bmatrix}7&-10\\-7&11\end{bmatrix} \\\\ X=\dfrac1{11}\left(4\begin{bmatrix}12&-3\\10&22\end{bmatrix}+\begin{bmatrix}7&-10\\-7&11\end{bmatrix}\right) \\\\ X=\dfrac1{11}\left(\begin{bmatrix}48&-12\\40&88\end{bmatrix}+\begin{bmatrix}7&-10\\-7&11\end{bmatrix}\right) \\\\ X=\dfrac1{11}\begin{bmatrix}55&-22\\33&99\end{bmatrix} \\\\ X=\begin{bmatrix}5&-2\\3&9\end{bmatrix}](https://tex.z-dn.net/?f=X%3D%5Cdfrac4%7B11%7D%5Cbegin%7Bbmatrix%7D12%26-3%5C%5C10%2622%5Cend%7Bbmatrix%7D%2B%5Cdfrac1%7B11%7D%5Cbegin%7Bbmatrix%7D7%26-10%5C%5C-7%2611%5Cend%7Bbmatrix%7D%20%5C%5C%5C%5C%20X%3D%5Cdfrac1%7B11%7D%5Cleft%284%5Cbegin%7Bbmatrix%7D12%26-3%5C%5C10%2622%5Cend%7Bbmatrix%7D%2B%5Cbegin%7Bbmatrix%7D7%26-10%5C%5C-7%2611%5Cend%7Bbmatrix%7D%5Cright%29%20%5C%5C%5C%5C%20X%3D%5Cdfrac1%7B11%7D%5Cleft%28%5Cbegin%7Bbmatrix%7D48%26-12%5C%5C40%2688%5Cend%7Bbmatrix%7D%2B%5Cbegin%7Bbmatrix%7D7%26-10%5C%5C-7%2611%5Cend%7Bbmatrix%7D%5Cright%29%20%5C%5C%5C%5C%20X%3D%5Cdfrac1%7B11%7D%5Cbegin%7Bbmatrix%7D55%26-22%5C%5C33%2699%5Cend%7Bbmatrix%7D%20%5C%5C%5C%5C%20X%3D%5Cbegin%7Bbmatrix%7D5%26-2%5C%5C3%269%5Cend%7Bbmatrix%7D)
Similarly, you would find
![Y=\begin{bmatrix}2&1\\4&4\end{bmatrix}](https://tex.z-dn.net/?f=Y%3D%5Cbegin%7Bbmatrix%7D2%261%5C%5C4%264%5Cend%7Bbmatrix%7D)
You can solve the second system in the same fashion. You would end up with
![P=\begin{bmatrix}2&-3\\0&1\end{bmatrix} \text{ and } Q=\begin{bmatrix}1&2\\3&-1\end{bmatrix}](https://tex.z-dn.net/?f=P%3D%5Cbegin%7Bbmatrix%7D2%26-3%5C%5C0%261%5Cend%7Bbmatrix%7D%20%5Ctext%7B%20and%20%7D%20Q%3D%5Cbegin%7Bbmatrix%7D1%262%5C%5C3%26-1%5Cend%7Bbmatrix%7D)
Answer:
9 * 10^16
Step-by-step explanation:
2 * 10^16
+7 * 10^16
9 * 10^16